Plotini opera - Plotinus (Oxonii : E Typographeo Clarendoniano, 1964)
3 volumes ; 20 cm; Includes bibliographical references and index of sources; t. 1. Porphyrii Vita Plotini. Enneades I-III -- t. 2. Enneades IV-V -- t. 3. Enneades VI
Keywords: Philosophy, Ancient